Rutinas de salud y síntomas emocionales en adultos durante el aislamiento social - MORENO TOCHIHUITL, MARICARMEN; Rodríguez-Santamaría, Yari; Juárez-Medina, Liliana Leticia; Márquez-Vargas, Patricia Marisol; Cadena-Santos, Francisco; Lerma-Valdez, Adriana (Acta Universitaria, 2022)
Social isolation as a security measure has forced the modification of family routines, favoring the presence of emotional conditions such as stress, anxiety, and depression. The objective of this study was to identify the relationship between family health routines and emotional symptoms (depression, anxiety, and stress) in adults on the border during social isolation. The study design was descriptive and correlational, where online surveys were applied to 149 volunteers. High health routines scores were found (M = 80.74, SD = 7.92), and younger participants reported more emotional symptoms (M = 14.86, SD = 14.38). Additionally, a negative relationship of health routines with anxiety symptoms (r = -0.236, p < 0.01) and depressive symptomatology (r = -0.191, p < 0.05) was found. It can be concluded that the better health routines around family needs, the lower the presence of emotional symptoms during isolation.